2 - What Should Globalisation Mean for African Humanities and Why? - Ugwuanyi, Lawrence Ogbo (Journal of Higher Education in Africa, 2022)
This work sets out to engage the ideology of globalisation by interrogating the notion of humanities that has been applied to study the concept. To do this, it addresses the following question: if the idea of globalisation was interrogated from the idea of man (being human)1 and studies of human nature informed by the values, principles and norms that define the idea of humankind from the African worldview, what would it amount to? What ideals would drive such a project and what difference would it make for the human community? To address these questions, the article will locate African humanities through what it calls the dominant humanities orientation in Africa, defined as the study of man (being human) available through the intellectual industry of modern Africa and inscribed through various subjects studied in the humanities in African institutions. Thereafter, it will proceed to locate what man (being human) would mean, assuming that effort is made to locate the meaning through the African endogenous worldview. The article will next proceed to articulate the gains of applying the African endogenous idea of man (being human) in articulating and directing globalisation. The method applied is an inductive analysis of views and positions in the humanities, African thought and globalisation.